1969
DOI: 10.1111/j.1440-169x.1969.00246.x
|View full text |Cite
|
Sign up to set email alerts
|

Cortical and Subcortical Changes Preceding Furrow Formation in the Cleavage of Newt Eggs

Abstract: In the first cleavage of the egg of the newt, Cynops(Triturus)pyrrhogaster,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

1971
1971
1998
1998

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…In the cleavage of amphibian eggs, the position of the cleavage plane is determined by the location of the FIC under the cortex (15,17,18), and the distribution of the FIC is determined by microtubules of the MA, as judged from the relationship between the position of the MA and the cleavage plane (8,22,23,30). Thus, the inhibition of furrow formation in the Exp.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the cleavage of amphibian eggs, the position of the cleavage plane is determined by the location of the FIC under the cortex (15,17,18), and the distribution of the FIC is determined by microtubules of the MA, as judged from the relationship between the position of the MA and the cleavage plane (8,22,23,30). Thus, the inhibition of furrow formation in the Exp.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, we have observed that the subcortical cytoplasm along the cleavage plane induces a furrow-like dent on the cortex when transplanted beneath the cortex in a region outside the cleavage plane (15,17,18), indicating that the subcortical cytoplasm along the cleavage plane contains some factor involved in furrow formation (furrow-inducing cytoplasm; FIC). Further, I have shown that the cortex acquires ability to form a furrow in response to the inductive activity of the FIC during cleavage (1 5, 17).…”
Section: Introductionmentioning
confidence: 99%
“…We have demonstrated that subcortical cytoplasm on a cleavage plane of amphibian eggs induces furrow-like dents when transplanted to a subcortical region outside the plane (Sawai, 1972(Sawai, , 1983Sawai et al, 1969). This indicates that subcortical cytoplasm on a cleavage plane contains a factor responsible for furrow formation, i.e.…”
Section: Introductionmentioning
confidence: 78%
“…We have shown by the FIC transplantation experiments (Sawai, 1972(Sawai, , 1983Sawai et al, 1969) that a furrow was established by an interaction of a cortical and a cytoplasmic factor . With regard to the relationship between the role of microtubule structures and that of the two factors in cortical events, several reports had indicated that microtubular poisons have no effect on the emergence of cortical changes such as travelling of a contractile wave, rounding-up of eggs or increase of stiffness (Hara et al, 1980;Sakai and Kubota, 1981;Sakai and Shinagawa, 1983;Shinagawa, 1983;Yoneda et al, 1982), which are regarded as a reflection of a cortical change indispensable for furrow formation (Sawai, 1979;Sawai and Yoneda, 1974).…”
Section: Discussionmentioning
confidence: 99%